Editorial [Hot Topic: Potential Application of Peptides in Tumor Targeting and Anticancer Therapeutics (Guest Editor: Jai Prakash)] - Prakash, Jai (Current Pharmaceutical Biotechnology, 2011)
Peptides own a high potential in the field of cancer because of their high target selectivity and vast applications. Tumor targeted drug delivery has increasingly become an essential step in anticancer therapies as conventional chemotherapies are accompanied with several limitations such as adverse effects and development of drug resistance. Among many targeting approaches, peptide-based carrier systems have contributed utmost in tumor targeting. Peptides have been substantially used in delivery of therapeutic drugs and genes to tumor and tumor-associated cells. In addition, conjugation of imaging probes to the tumor-specific peptides or peptide-based carriers promoted their application for tumor diagnostics. Peptides themselves can also serve as anticancer agents. Peptides can be rationally designed for their high selectivity to a target and can be easily produced with chemical or recombinant techniques. In addition, peptides have lower/no immunogenicity, higher tissue permeability, and stronger affinity to the receptors compared to other targeting agents such as monoclonal antibodies. This special issue focuses on the peptide designing with novel methods and application of the peptides in tumor targeted delivery as well as their potential use as anticancer agents. Designing of peptides can be approached by various methods such as in silico and Phage-display methods. In this issue, Sadatmousavi and coworkers have included many peptide-designing methods in their article on self-assembling peptides and enlisted a range of peptides derived from these methods. As a part of a review on anti-angiogenic peptides, Rosca and coworkers have also contributed a special section on computational approaches for peptide discovery. To have a focus on peptide discovery, Pirogova and coworkers have introduced a novel method of Resonant Recognition model (RRM) to design the bioactive peptides. RRM frequencies represent the characteristic features of different proteins biological functions and interactions to their targets. Examples of peptide mimicking IL-12 activity and an antagonistic peptide for bFGF have been presented in this paper including bioactivity analyses of RRM-IL-12 peptide. Tumor targeted delivery of anticancer drugs is highly challenging as several barriers have to be crossed in order to reach in tumors. During tumor development, tumor cells recruit new blood vessels through neoangiogenesis and supply nutrition to the tumor. Corti and Curnis have contributed an interesting review on the targeting to tumor vasculature using NGR peptide against CD13. Many variables of this peptide were synthesized and used for delivery of chemotherapeutic agents, cytokines, viral particles, nucleic acids. Authors have published many research articles in this area and also summarized their potential findings in this review. Garg and Kokkoli, in this issue, have contributed a research article in which they experimentally demonstrated the application of a fibronectin-mimetic peptide for tumor targeting to α5β1 integrin. The α5β1 integrin is a transmembrane protein that is expressed on many tumor types and mediates interaction between adjacent cells and/or the extracellular matrix. This peptide was conjugated to pH-sensitive PEGylated liposomes that control the release of encapsulated drug within lysosomes where pH drops down. They also showed that peptide can induce intracellular delivery of calcein-loaded liposomes and the loaded drug could be released in short time. These data demonstrate that peptides can be applied to bring large carriers into tumor cells. Tumors derived from reproductive organs such as ovarian, prostate, breast and endometrial express hormonal receptors that are specifically expressed on tumor cells of these organs. Zhang and Xu have focused their review on the application of hormone peptides in tumor targeting. They have thoroughly discussed the application of the peptides binding to the receptors for luteinizing hormone-releasing hormone (LHRH), follicle-stimulating hormones (FSH), and luteinizing hormone (LH). Application of these peptides in delivering anticancer agents or siRNA either by direct conjugation or with the help of a carrier has been discussed in detail. In addition to the above mentioned tumor targeting peptides, Sadatmousavi and coworkers have presented an excellent review on the role of self-assembling peptides in tumor targeting. Self-assembling peptide have been potentially used as carriers for drug/gene delivery. They can be rationally tuned to form a variety of stable nanostructures e.g. fibers, rods, tubes, nanovesicles and globules. Self-assembling peptides include peptide amphiphile, bolaamphiphile peptides, cyclic peptides and ioniccomplementary peptides are the main classes. These peptides can form β-sheet, α-helix and random coil secondary structures and can respond to change in pH, temperature, and ionic strength by altering their macromolecular structure. Tumor environment has a lower pH due to hypoxia and higher temperature than normal tissue, and these stimuli therefore make selfassembling peptides an interesting agent for providing controlled release of therapeutic agents within tumors. Authors have significantly extended the research area, and this review summarizes their and others' research work. Intracellular delivery of therapeutic proteins, nucleic acids, and polymers is a major hurdle for their effectivity. Receptormediated internalization is one of the processes for intracellular delivery but yet limited by the endosomal escaping barriers for some agents such as small RNA. Potential role of the receptor binding peptides has already been discussed above. Other type of peptides are cell penetrating peptides (CPP) which facilitate the intracellular delivery in a different manner. In this issue, Choi and coworkers have contributed an excellent review on CPP and their applications in tumor targeting. This review includes the detailed information on different types of CPP such as TAT, penetratin, transportan, pep-1 and many others which used so far in tumor field. They have described mechanism of action of these peptides including some practical details. Many sections of this article explain the potential utility of CPP in intracellular delivery of therapeutic proteins, siRNA and polymeric drugs into tumor cells. One can appreciate the elaborated figures explaining the mechanisms in an easy way as well as detailed text providing the up-to-date information on the literature over these therapeutic agents. Use of peptides is not limited to tumor targeted delivery but they can themselves serve as anticancer agents. This issue comprises two articles focused on peptide application as therapeutic agents. Barras and Widmann have contributed a detailed review on the apoptosis-inducing peptides for cancer therapy. During apoptosis, cells undergo shrinking and cleave their DNA and make apoptotic bodies which follows with their disposal by phagocytes or other cells. Induction of this process in tumor cells can generate tumor therapeutics. Balance between pro-apoptotic and anti-apoptotic factors lead to the decision of cell death, which is mainly controlled by Bcl-2 family proteins and some other regulatory proteins such as IAP, Smac and p53. Authors have meticulously described the peptides derived from Bcl-2 family (Bak, PUMA, Bad, Bid, Bim), IAPs- and Smacderived and p53-derived peptides as well as many natural peptides. Formation of tumor vasculature (angiogenesis) is the most essential process for tumor growth without which the tumor cannot grow. Therefore, interruption in this process using anti-angiogenic peptides can lead to the inhibition of tumor growth. The group of Prof. Popel has significantly contributed to the field of anti-angiogenic peptides and added an excellent review on the same topic in this issue (Rosca et al). They have comprehensively enlisted the peptides that have been shown to suppress tumor angiogenesis in pre-clinical models or are in clinical stages. Angiogenesis is a complex process in which tumor cells recruit endothelial cells by releasing growth factors and chemokines. These recruited cells interact with extracellular matrix (ECM) protein through their integrin receptors and complete blood vessels formation. This cascade can be interfered at various stages using peptides derived from the participating proteins. Rosca and colleagues have nicely presented anti-angiogenic peptides based on their origin e.g. ECM, growth factors, chemokines, coagulation factors etc. Not limited to this, authors have included a large section on designing and optimization of anti-angiogenic peptides for cancer applications. Developing these peptides to pharmaceutical product is the next biggest challenge, and a strategic development plan and possible solutions to overcome many associated problems have also been discussed. In summary, this special issue provides a comprehensive knowledge on the applications of peptides for tumor targeting and as anticancer therapies.